2021
DOI: 10.3390/mi12070794
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility of SU-8 and Its Biomedical Device Applications

Abstract: SU-8 is an epoxy-based, negative-tone photoresist that has been extensively utilized to fabricate myriads of devices including biomedical devices in the recent years. This paper first reviews the biocompatibility of SU-8 for in vitro and in vivo applications. Surface modification techniques as well as various biomedical applications based on SU-8 are also discussed. Although SU-8 might not be completely biocompatible, existing surface modification techniques, such as O2 plasma treatment or grafting of biocompa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 76 publications
0
28
0
Order By: Relevance
“…The study provides a comprehensive understanding of bacterial−SU-8 surface interaction, which could help design effective strategies for the fabrication of SU-8based various unique devices for biomedical applications. [6][7][8][9]12 ■ CONCLUSIONS In summary, our study elucidates the surface changes of SU-8 thin films governed by wettability and surface carboxylic groups and how such properties influence bacterial motility, adhesion, and subsequent colonization in a spatiotemporal manner. The enhancement of the motility and direction of X. fastidiosa single cells on carboxylated surfaces during the initial stages of growth has been observed.…”
Section: ■ Results and Discussionmentioning
confidence: 96%
“…The study provides a comprehensive understanding of bacterial−SU-8 surface interaction, which could help design effective strategies for the fabrication of SU-8based various unique devices for biomedical applications. [6][7][8][9]12 ■ CONCLUSIONS In summary, our study elucidates the surface changes of SU-8 thin films governed by wettability and surface carboxylic groups and how such properties influence bacterial motility, adhesion, and subsequent colonization in a spatiotemporal manner. The enhancement of the motility and direction of X. fastidiosa single cells on carboxylated surfaces during the initial stages of growth has been observed.…”
Section: ■ Results and Discussionmentioning
confidence: 96%
“…It is known that the water contact angle affects the biocompatibility and the lower the water contact angle, the higher the biocompatibility. 43,44 It was analyzed that the water contact angles of MNs, Dox MNs, and Chi/Dox MNs surfaces with hydrophilic surfaces were 80.66 ± 1.08 , 55.35 ± 0.22 and 45.16 ± 0.19 , respectively (Table 1). Thus, it is observed that the contact angle of Chi/Dox MNs is successfully reduced compared to MNs and Dox/MNs samples.…”
Section: Resultsmentioning
confidence: 99%
“…The 16-channel MEA uses SU-8 as the insulating substrate and Pt as the conductive material. SU-8 has been extensively utilized in biomedical devices due to its high transparency, low young's modulus, and high yield strength [54][55][56]. Pt is a common material for stimulation electrodes for its chemical inertness [57][58][59].…”
Section: Resultsmentioning
confidence: 99%